EVALUATION OF HIGH YIELDING TEMPERATE PERENNIAL FORAGES FOR AUGMENTING FORAGE RESOURCES IN LADAKH (INDIA) (Applied Biological Research, 2023)
The present study was conducted in a community pastureland of Spituk  Monastery, Leh (Ladakh) from 2013 to 2015 to evaluate some temperate  forage grasses/legumes and their mixtures grown in the interspaces of Salix  plantation with a spacing of 4 m x 4 m. The experiment comprised of 13  treatments laid out in a randomized block design with each treatment  replicated three times using a plot size of 12 m x 12 m. The results revealed  that alfalfhad maximum value of sward height (62.5 cm), which was at par  with treatment alfalfa grown in mixture with Dactylis  tall fescue +  sainfoin. However, plant cover was maximum (75.6-85.6%) in mixture  treatments as compared to sole grass or legume treatments (20.4-80.6%).  Maximum green (9.87 t ha-1) and dry fodder yield (2.68 t ha-1) was observed  in Dactylis + tall fescue + sainfoin + alfalfa treatment, which was at par with  tall fescue + alfalfa treatment. The mean values for plant height, collar  diameter, diameter at breast height, number of branches and leaf yield were 1.79 m, 21.2 mm, 16.1 mm, 5.32 and 66.72 dry matter kg ha-1, respectively.  The study suggests that tall fescue, Dactylis, red clover and sainfoin hold  great promise as intercrop in Salix-based silvipastoral systems for der needs in the region.
Keywords: Evaluation; grasses/legumes; Ladakh; Salix; silvipasture